PEMBANGUNAN DAN PERUBAHAN: DAMPAK PERUMAHAN TERHADAP KEHIDUPAN MASYARAKAT ASLI DI KELURAHAN TAMANGAPA KOTA MAKASSAR - Sakmawati Sakmawati; Shasliani Shasliani; Hasni Hasni; Asmaul Husna Amiruddin; Ulul Azmi Mustari (Universitas Negeri Makassar, 2026)
One of the areas located on the outskirts of a major city and experiencing the impacts of rapid housing development is Subdistrict Tamangapa, District Manggala, Makassar City. The total area of Tamangapa Subdistrict is 6,062 hectares, of which 4,499 hectares are agricultural land. Lands that were once used for agriculture or left as open fields have now been converted into modern residential complexes. This transformation has brought various consequences for the local community, particularly in economic and social aspects. The research method employed in this study is qualitative, utilizing observation, interviews, and documentation techniques for data collection. The findings indicate that housing development has led to significant changes in the economic and social life of the community. From an economic perspective, housing development has created new employment opportunities, such as in construction and services, which have been positively utilized by the local residents. A shift in livelihood from the agrarian sector to the informal or service sector has become an inevitable reality that the community must adapt to. From a social perspective, housing development has created a social divide between newcomers and indigenous residents, both in terms of social interactions and access to social facilities. This can be observed in the modern lifestyle brought by the new residents, which at times does not align with the traditional values upheld by the local community.